A Type VI Secretion System Trans-Kingdom Effector Is Required for the Delivery of a Novel Antibacterial Toxin in Pseudomonas aeruginosa - Berni, Benjamin; Soscia, Chantal; Djermoun, Sarah; Ize, Bérengère; Bleves, Sophie (Frontiers in Microbiology, 2019)
Pseudomonas aeruginosa has evolved multiple strategies to disarm and take advantage of its host. For this purpose this opportunist pathogen has particularly developed protein secretion in the surrounding medium or injection into host cells. Among this, the Type VI Secretion System (T6SS) is utilized to deliver effectors into eukaryotic host as well as target bacteria. It assembles into a contractile bacteriophage tail-like structure that functions like a crossbow, injecting an arrow loaded with effectors into the target cell. The repertoire of T6SS antibacterial effectors of P. aeruginosa is remarkably broad to promote environmental adaptation and survival in various bacterial communities, and presumably in the eukaryotic host too. Here we report the discovery of a novel pair of antibacterial effector and immunity of P. aeruginosa, Tle3 and Tli3. Tli3 neutralizes the toxicity of Tle3 in the periplasm to protect from fratricide intoxication. The characterization of the secretion mechanism of Tle3 indicates that it requires a cytoplasmic adaptor, Tla3, to be targeted and loaded onto the VgrG2b spike and thus delivered by the H2-T6SS machinery. Tla3 is different from the other adaptors discovered so far, and defines a novel family among T6SS with a DUF2875. Interestingly this led us to discover that VgrG2b that we previously characterized as an anti-eukaryotic effector possesses an antibacterial activity as well, as it is toxic towards Escherichia coli. Excitingly Tli3 can counteract VgrG2b toxicity. VgrG2b is thus a novel trans-kingdom effector targeting both bacteria and eukaryotes. VgrG2b represents an interesting target for fighting against P. aeruginosa in the environment and in the context of host infection.